2013
DOI: 10.1016/j.annepidem.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health: associations with race–ethnicity, nativity, and education in a diverse, population-based sample of Californians

Abstract: Purpose This study examined how race-ethnicity, nativity, and education interact to influence disparities in cardiovascular (CV) health, a new concept defined by the American Heart Association (AHA). We assessed whether race-ethnicity and nativity disparities in CV health vary by education, and whether the foreign-born differ in CV health from their US-born race-ethnic counterparts with comparable education. Methods We used data from the 2009 California Health Interview Survey to determine the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…23 CVH has been strongly predictive of cardiovascular events and mortality in multi-ethnic populations 31,46-48 but longitudinal changes in the score, and associations with time in US, have rarely been examined. 49,50 Third, we examined differences in these associations between younger and older immigrants. From a life course perspective, it is difficult to disentangle effects of age at immigration from those of length of US residence because of their linear dependency (length of US residence = age – age at immigration).…”
Section: Discussionmentioning
confidence: 99%
“…23 CVH has been strongly predictive of cardiovascular events and mortality in multi-ethnic populations 31,46-48 but longitudinal changes in the score, and associations with time in US, have rarely been examined. 49,50 Third, we examined differences in these associations between younger and older immigrants. From a life course perspective, it is difficult to disentangle effects of age at immigration from those of length of US residence because of their linear dependency (length of US residence = age – age at immigration).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of cardiovascular health, as measured with CVHI, has been examined in various populations globally and within the United States in both adults and adolescents . “Ideal” CVHI is associated with decreased CVD and decreased risk of death .…”
Section: Introductionmentioning
confidence: 99%
“…and within the United States in both adults [13][14][15][16][17] and adolescents. 18 "Ideal" CVHI is associated with decreased CVD 17,19,20 and decreased risk of death.…”
mentioning
confidence: 99%
“…Research in California has shown low F&V intake among all adults; college-educated native- and foreign-born Asians had fewer servings of F&Vs than their less-educated counterparts (Bostean et al, 2013). Due to the limitations of the measures, reasons for low F&V intake among our sample are unclear.…”
Section: Discussionmentioning
confidence: 99%